Implementation of Basel – II Accord in India (Implications for Banking Governance) - Raja, M; Sudharhar, J. Clement (Journal of Commerce and Trade, 2009)
Basel II is the recommendations on banking laws and regulations issued by the Basel Committee on Banking Supervision. The purpose of Basel II, in June 2004, is to create an international standard that banking regulators about how much capital banks need to put aside to guard against the types of financial and operational risks. Advocates of Basel II believe that such an international standard can help protect the international financial system from problems that might arise should a major bank or a series of banks collapse. In practice, Basel II attempts to setting up rigorous risk and capital management system. This requires the banker, to establish the mechanism to capital reserves, bank risk exposes, lending and investment practices. Generally speaking, the greater the amount of capital the bank needs to hold to safeguard its solvency and overall economic stability. India is also not exempted from this risk because it agreed to implement the Basel-II by 2008. With this background the present study is an attempt to provide a prelude to the implementation norms of Basel Accord-II in India and its implication for the concomitant corporate governance policies of banking sector.